Active Distance Learning to Improve Kindergarten Teachers' Computatitonal Thingking Skills - Hasjiandito, Akaat; Waluyo, Edi; Nugroho, Agustinus Arum Eka; Wantoro, Wantoro; Listanto, Virgiawan (PIAUD Universitas Islam Negeri Sunan Kudus, 2022)
Computational thinking is an essential concept that has attracted the attention of early childhood educators over the last decade. However, not all kindergarten teachers have yet obtained information and ideas related to computational thinking skills. This study attempts to determine the effectiveness of active distance learning using a zoom video conference application in improving teachers' computational thinking skills. Furthermore, it also examines the teachers' progress in learning computational skills through online coding websites such as code.org and ScratchJr. A hundred and sixty-three kindergarten teachers from Central Java Province in Indonesia participated in the study. The study used a quantitative approach and employed a pre-experimental design, one group pretest and a post-test study. The data were gathered through pretest, post-test, and reflection of assignment records. We employed the Wilcoxon test because our data are on the ordinal scale. Wilcoxon signed-rank test was utilized to find out the significance of distance learning. The results show active distance learning effectively enhances teachers' computational thinking skills. Moreover, active distance learning provides an impressive experience to participants in improving their mastery of computational thinking.